Infective Outcomes of Semi-Rigid Ureteroscopy in Patients With Positive Preoperative Leucocyte Esterase: A Retrospective Analysis - Mohamad, Abdul Malek; Mohamed Sufian, Mohamad 'Arif Rukaini; Kamarulzaman, Mohd Nazli; Ab Rashid, Islah Munjih (The Interventionalist Journal, 2026)
Background: Ureteroscopy is the standard of care for ureteral diseases such as urolithiasis, yet it carries the risk of postoperative infectious complications.¹,² Screening for urinary tract infection via leucocyte esterase on dipstick is routine; however, LE can be false-positive in the presence of stone-related inflammation, creating a dilemma when urine culture and sensitivity results are not immediately available.³ We aim to evaluate the safety and outcomes of proceeding with semi-rigid URS based on clinical findings and dipstick parameters while C&S results are retrospectively reviewed. Methods: This retrospective cohort study analyzed 231 patients who underwent semi-rigid URS at Sultan Ahmad Shah Medical Centre between December 2018 and December 2023. All included patients had positive preoperative LE but negative nitrite and no clinical signs of infection. Surgical timing was determined by dipstick findings rather than awaiting C&S results, with culture data analyzed retrospectively. Results: Postoperative urinary tract infection occurred in 16 patients. Only 18 patients had positive urine cultures upon retrospective review, indicating a 92.2% discrepancy rate between LE positivity and true bacteriuria. Multivariate logistic regression identified retrospectively positive urine culture and prior history of UTI as independent predictors of postoperative infection. Conclusion: Semi-rigid URS can be performed safely in patients with positive preoperative LE when clinical assessment and negative nitrite support proceeding, even before culture results are known. The high discrepancy between LE and C&S supports a pragmatic approach of not delaying surgery for LE positivity alone, while retrospective C&S data serves effectively for postoperative risk stratification.